2019
DOI: 10.1111/jocn.14934
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of nurses’ willingness to receive vaccines: Application of the health belief model

Abstract: Aims and objectives To assess the willingness of nurses to receive vaccines as recommended by Taiwan's “Immunization Recommendations for Healthcare Personnel” (IRHCP), as well as the factors associated with their willingness. Background Immunisation for healthcare personnel (HCP) is a means of reducing pathogen transmission. Also, vaccinating HCP reduces personnel and labour costs during an epidemic. Methods A cross‐sectional study was conducted. A self‐administered questionnaire survey targeting nurses workin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…Cues to action include information, people, and events that nudge the individual towards vaccination. The HBM has been adopted as a conceptual framework that has been used to evaluate the beliefs and attitudes toward a diversity of vaccines including the influenza, human papillomavirus, and hepatitis B vaccines ( Teitler-Regev, Shahrabani & Benzion, 2011 ; Donadiki et al, 2014 ; Hu et al, 2017 ; Chen et al, 2019 ). Moreover, several studies have shown that the HBM constructs can serve as an important predictor of influenza vaccination uptake ( Brewer et al, 2007 ; Shahrabani, Benzion & Yom Din, 2009 ; Shahrabani & Benzion, 2010 ; Tsutsui, Benzion & Shahrabani, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cues to action include information, people, and events that nudge the individual towards vaccination. The HBM has been adopted as a conceptual framework that has been used to evaluate the beliefs and attitudes toward a diversity of vaccines including the influenza, human papillomavirus, and hepatitis B vaccines ( Teitler-Regev, Shahrabani & Benzion, 2011 ; Donadiki et al, 2014 ; Hu et al, 2017 ; Chen et al, 2019 ). Moreover, several studies have shown that the HBM constructs can serve as an important predictor of influenza vaccination uptake ( Brewer et al, 2007 ; Shahrabani, Benzion & Yom Din, 2009 ; Shahrabani & Benzion, 2010 ; Tsutsui, Benzion & Shahrabani, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…The health belief model (HBM) is a model constructed based on the assumption that people are likely to take disease prevention behaviors and interventions (e.g., vaccination) if there is sufficient motivation (e.g., the perception that they are susceptible to the disease, the disease is severe, the behavior is beneficial, and barriers are minimal) and cues to action (e.g., recommendations from family members and healthcare workers) (26). It has been adopted as a conceptual framework that was widely used to evaluate the beliefs and attitudes toward vaccines (e.g., influenza vaccines, COVID-19 vaccines, human papillomavirus vaccines, and hepatitis B vaccines) and explain and predict vaccination behaviors (17,(27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%
“…Administrators should ensure that all policies are communicated to staff and the school population to yield the best results. Increased staff knowledge regarding vaccine policies and recommendations is a significant predictor of vaccination willingness and compliance (Chen et al, 2019).…”
Section: Implications For Educators and Schoolsmentioning
confidence: 99%